CORPORATE SOCIAL RESPONSIBILITY AND PERFORMANCE OF FIRMS IN LAGOS STATE, NIGERIA - Kayode David KOLAWOLE (Gusau Journal of Accounting and Finance)
Corporate social responsibility (CSR) is widely practiced by multinational companies in developed countries. But Nigerian companies are not widely accepted the concept. Hence, this study examines the impact of CSR on the performance of companies in Lagos State. The study used primary data collected through a questionnaire survey. Ordered logit and Structural Equation Modelling method of multiple regressions was used to analyze the data obtained. The results indicate that educational accountability has a positive, statistically significant effect on service delivery at the 1% significance level. Environmental responsibility was also found to have a significant impact on service delivery. Ethical responsibility also shows a significant effect of service provision at the 1% level of significance. Additionally, a significant effect of service provision is found at the 1% level of financial responsibility. The study concludes that CSR plays an important role in increasing the performance of companies in Lagos State. Nigeria. For this reason, it is recommended that companies should prioritize education and CSR initiatives as these have been identified as key drivers of improved and sustainable customer service.